Analyzing National Responses to COVID-19 Pandemic using STPA. (June 2021) - Chen, Shufeng; Khastgir, Siddartha; Jennings, Paul
Abstract: The unprecedented COVID-19 pandemic has affected most aspects of human life, including the ways in which organizations are operating. Minimizing the spread of coronavirus and its economic consequences, and creating a new and safe lifestyle has now become the common goals of governments all over the world. Although governments have responded to the COVID-19 pandemic by implementing various rules while interacting with relevant organizations to provide health service, vaccine research, and production of essential items, the complexities in the interactions between various stakeholders have proved to be challenging to have efficient and timely outputs. When different stakeholders (i.e. governments, organizations, and the public) are interacting with each other, a systems thinking process needs to be applied to capture the nuances of the interactions and the subsequent emergent behavior to effectively contribute to the system output (i.e. a safer way of life). This paper applied a system-thinking-inspired process called System Theoretic Process Analysis (STPA) to analyze the current response to the COVID-19 pandemic. The analysis treated various stakeholders as a part of the system, and it focused on the interactions among different stakeholders (i.e. functional blocks) within the system - i.e. 'Government', 'Foreign Governments', 'Organizations', and 'General Public', as well as the interactions with 'W.H.O'. The STPA analysis found 236 potential Unsafe Control Actions (UCAs) (or unsafe interactions) among the stakeholder interactions, each of the UCAs was then further analyzed. In total 1440 causal factors of the UCAs were identified, and 2880 requirements were proposed to avoid such unsafe interactions.